Produktdesign und Semi-Statische Absicherung von Turbo-Zertifikaten - Antje Mahayni; Michael Suchanecki (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Turbo-Certificates are one of the most popular structured equity products for private investors in Germany. They can be regarded as special forms of barrier options. The relation between the barrier level and the strike price is especially important for the design of these products. By using a certain choice of these parameters, the issuer is able to obtain an almost static (super-) hedge in standard option contracts. If the barrier level is equal to the strike, the upper price bound of a Turbo-Long-Certificate coincides with the value of a forward contract. Therefore, in the case of a Turbo-Short-Certificate, the forward implies only a lower price bound. It is shown that in general, the issuer can neither hedge a single certificate nor a portfolio of certificates without using standard options.
Keywords: G10; G21; G13; 330; Turbo-Zertifikate; Put-Call-Symmetrie; Static Hedging; Barrier-Optionen; Produktdesign; Barrier Options; Produktdesign; Black-Scholes-Modell; Optionspreistheorie